Pharmacokinetics of intramuscular tranexamic acid in bleeding trauma patients: a clinical trial. (January 2021) - Grassin-Delyle, Stanislas; Shakur-Still, Haleema; Picetti, Roberto; Frimley, Lauren; Jarman, Heather; Davenport, Ross; McGuinness, William; Moss, Phil; Pott, Jason; Tai, Nigel; Lamy, Elodie; Urien, Saïk; et al.
Abstract: Background: Intravenous tranexamic acid (TXA) reduces bleeding deaths after injury and childbirth. It is most effective when given early. In many countries, pre-hospital care is provided by people who cannot give i.v. injections. We examined the pharmacokinetics of intramuscular TXA in bleeding trauma patients. Methods: We conducted an open-label pharmacokinetic study in two UK hospitals. Thirty bleeding trauma patients received a loading dose of TXA 1 g i.v., as per guidelines. The second TXA dose was given as two 5 ml (0·5 g each) i.m. injections. We collected blood at intervals and monitored injection sites. We measured TXA concentrations using liquid chromatography coupled to mass spectrometry. We assessed the concentration time course using non-linear mixed-effect models with age, sex, ethnicity, body weight, type of injury, signs of shock, and glomerular filtration rate as possible covariates. Results: Intramuscular TXA was well tolerated with only mild injection site reactions. A two-compartment open model with first-order absorption and elimination best described the data. For a 70-kg patient, aged 44 yr without signs of shock, the population estimates were 1.94 h −1 for i.m. absorption constant, 0.77 for i.m. bioavailability, 7.1 L h −1 for elimination clearance, 11.7 L h −1 for inter-compartmental clearance, 16.1 L volume of central compartment, and 9.4 L volume of the peripheral compartment. The time to reach therapeutic concentrations (5 or 10 mg L −1 ) after a single intramuscular TXA 1 g injection are 4 or 11 min, with the time above these concentrations being 10 or 5.6 h, respectively. Conclusions: In bleeding trauma patients, intramuscular TXA is well tolerated and rapidly absorbed. Clinical trial registration: 2019-000898-23 (EudraCT); NCT03875937 (ClinicalTrials.gov ).